Perceptions of oocyte banking from women intending to circumvent age‐related fertility decline. (14th October 2016) - de Groot, Marije; Dancet, Eline; Repping, Sjoerd; Goddijn, Mariette; Stoop, Dominic; van der Veen, Fulco; Gerrits, Trudie
Abstract: Introduction: Women can now opt to bank their oocytes with the intention of increasing their chances of achieving a pregnancy after their fertility has declined. This exploratory study aimed to gain insight into how women, considering oocyte banking to circumvent age‐related fertility decline, perceive this intervention. Material and methods: We conducted a qualitative study in a Dutch university medical center and held in‐depth interviews with women on the waiting list for oocyte banking. We recorded the interviews, transcribed them verbatim and used thematic analysis. Results: All women were financially independent and lived in single‐person urban households. They opted for oocyte banking because they wished to share parenthood with a future partner rather than becoming a single parent. This strong desire was key in their interpretation of all aspects of the intervention. Women set aside information about the limited success rates and potential risks, as they were optimistic about their own prognosis, thought that the chances for success were equally likely as the chances it would fail, and because of "anticipatory regret". They perceived oocyte banking as a "helping hand" to achieve shared parenthood. Although women found the costs of the intervention high, they were willing to invest their money to increase their chances for shared parenthood. Conclusions: Oocyte banking allows women to circumvent age‐related fertility decline. The prospect of potential shared parenthood overrules the perceived health risks and burden. Health professionals should take this into account when informing potential users of oocyte banking.